Strategi Manajemen Risiko Terintegrasi Berdasarkan ISO 31000:2018 pada Industri Properti - Dewi Lestyowati; Said Kelana Asnawi (Jurnal Manajemen, 2025)
This study aims to analyze an integrated risk management system based on Enterprise Risk Management (ERM) in accordance with ISO 31000:2018 for the management of The Kensington Royal Suites Apartment. Risk management plays an important role in sustaining apartment operations in the property industry, which is exposed to financial, operational, legal compliance, occupational safety and health, and reputational risks. This study employed an exploratory approach using Value Chain Analysis, PESTEL Analysis, and stakeholder analysis supported by a literature review. The proposed ERM framework refers to ISO 31000:2018 by integrating eight risk management principles with the organization's core values, namely CARING (Commitment, Agility, Care, Integrity, Collaboration, and Gratitude). The framework also integrates three main aspects: compliance, internal control, and risk management, and is implemented through the Balanced Scorecard (BSC) framework. The study identified 85 risk events, of which 25 exceeded the organization’s risk tolerance limit. After implementing the proposed risk treatment strategies, all risks were reduced to within the acceptable risk appetite of the organization. The implementation of ERM based on ISO 31000:2018 is expected to enhance the management’s capability in mitigating risks, strengthening strategic management value, and improving stakeholders’ trust in service quality.